Sirtuin 1 activator alleviated lethal inflammatory injury via promotion of autophagic degradation of pyruvate kinase M2 - Zhao, Shuang; Sun, Yili; Wu, Xicheng; Yang, Yongqiang; Fan, Kerui; Hu, Kai; Qin, Yasha; Li, Kexin; Lin, Ling; Chen, Kun; Ma, Yuhua; Zhu, Min; et al. (Frontiers in Pharmacology, 2023)
Upregulation of pyruvate kinase M2 (PKM2) is critical for the orchestration of metabolism and inflammation in critical illness, while autophagic degradation is a recently revealed mechanism that counter-regulates PKM2. Accumulating evidence suggests that sirtuin 1 (SIRT1) function as a crucial regulator in autophagy. The present study investigated whether SIRT1 activator would downregulate PKM2 in lethal endotoxemia via promotion of its autophagic degradation. The results indicated that lethal dose of lipopolysaccharide (LPS) exposure decreased the level of SIRT1. Treatment with SRT2104, a SIRT1 activator, reversed LPS-induced downregulation of LC3B-II and upregulation of p62, which was associated with reduced level of PKM2. Activation of autophagy by rapamycin also resulted in reduction of PKM2. The decline of PKM2 in SRT2104-treated mice was accompanied with compromised inflammatory response, alleviated lung injury, suppressed elevation of blood urea nitrogen (BUN) and brain natriuretic peptide (BNP), and improved survival of the experimental animals. In addition, co-administration of 3-methyladenine, an autophagy inhibitor, or Bafilomycin A1, a lysosome inhibitor, abolished the suppressive effects of SRT2104 on PKM2 abundance, inflammatory response and multiple organ injury. Therefore, promotion of autophagic degradation of PKM2 might be a novel mechanism underlying the anti-inflammatory benefits of SIRT1 activator.